(untitled) (Journal of the College of Basic Education, 2026)
The current research aimed to know the effect of the 4H strategy on critical thinking of the sixth grade of primary Pupils in mathematics. The research sample included (50) Pupil from the sixth grade of primary Pupils , divided into two groups, one experimental and the other control. A critical thinking test was prepared and its psychometric properties were verified. The research concluded that teaching according to the 4H strategy provided Pupils with critical thinking skills by developing their abilities to analyze, interpret, and verify the validity of results. It recommended including critical thinking skills in mathematics books, especially at the primary level, and suggested conducting a study to know the effect of the 4H strategy on other patterns of thinking such as creative thinking and mathematical thinking.